ANALISIS PENERAPAN PRINSIP PENYAJIAN DAN PENGUNGKAPAN STANDAR AKUNTANSI KEUANGAN INDONESIA TENTANG KOMBINASI BISNIS PADA LAPORAN KEUANGAN PT TELEKOMUNIKASI INONESIA (PERSERO) TBK PERIODE 2012-2014 - Maimunah, Siti (Universitas Pakuan, 2016)
Presentation of the value of intangible assets recorded on the financial statements of PT Telekomunikasi Indonesia (Persero) Tbk, there is the value of goodwill should be presented separately to intangible assets. Presentation of goodwill which is not separated from intangible assets to become a problem for the users of financial statements to understand the content of those statements. This study aims to determine how the process of business combinations on the PT Telekomunikasi Indonesia (Persero) Tbk. The study uses secondary data from annual reports and financial statements of the period of 2012 through 2014, and primary data in the form of a questionnaire as a proponent of the theory applied by the researchers so that research will be measurable and objective. The results of this study indicate that goodwill is initially measured at cost, being the excess of the aggregate of the consideration transferred and the value that is recognized by the non-controlling interest and goodwill are presented in the statement of the position of non-current assets kuangan section. PT Telekomunikasi Indonesia (Persero) Tbk in the presentation of its financial statements as a whole in accordance with the standards set, but in the activities of the business combination of PT Telekomunikasi Indonesia (Persero) has not been fully in accordance with IAS 22 revised 2010 from the acquisition resulted in goodwill activities. Goodwill should have been presented in the consolidated statement of financial position on the part of non-current assets separately to other intangible assets.Â Keywords: Business combinations, acquisitions, goodwill, fair value.